SEEING THEMSELVES AS TEACHERS: PRESERVICE TEACHERS’ DEVELOPMENT OF TEACHER IDENTIFY AND SELF-EFFICACY WITH THE EARLY FIELD EXPERIECE - Iwai, Yuko (International Online Journal of Education and Teaching, 2025)
This study examines forty-eight preservice teachers’ teacher identity and self-efficacy during their first field experience in an elementary Professional Development School (PDS) site. They engaged in three half-day field experiences per week, observed their mentor teachers’ lessons, developed and taught lessons, and reflected on their field experience during one semester. Data including pre- and post-surveys on teacher identity and self-efficacy, reflection journals, written commentaries for planning ELA lessons, and written reflection commentaries about delivery of ELA lessons, were collected to examine their development of teacher identity and self-efficacy. By the end of the field experience, they reported more confidence in engaging students in learning. They also reported that they developed instructional strategies to teach content and to manage the classroom. Field experience plays a key role in shaping preservice teachers’ professional identity. Hands-on experiences in the classroom offered them opportunities to develop their self-efficacy in student engagement, instructional strategies, and classroom management. Implications for teacher educators and teacher education preparation programs are included.